2021
DOI: 10.3390/jcm10184236
|View full text |Cite
|
Sign up to set email alerts
|

Hypertriglyceridemia Is Associated with More Severe Histological Glomerulosclerosis in IgA Nephropathy

Abstract: IgA nephropathy (IgAN) is a globally well-known primary glomerular nephropathy. Hypertriglyceridemia (HTG) is one factor contributing to atherosclerosis and is a common complication of renal failure. HTG is a significant risk factor for decreased renal function in patients with IgAN. We evaluated the association of HTG with the histopathological features of IgAN patients. A total of 480 patients diagnosed with IgAN via kidney biopsy from eight university hospitals affiliated with the College of Medicine of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…33 C3 deposits were first detected from IMN in 1984. 16,17 Patients with glomerular C3 deposits have proteinuria with a more severe symptom, which supports the relationship between complement activation and severity of IMN. 17 The greater deposition of C3 predicts a poor prognosis of glomerular disease.…”
mentioning
confidence: 59%
See 2 more Smart Citations
“…33 C3 deposits were first detected from IMN in 1984. 16,17 Patients with glomerular C3 deposits have proteinuria with a more severe symptom, which supports the relationship between complement activation and severity of IMN. 17 The greater deposition of C3 predicts a poor prognosis of glomerular disease.…”
mentioning
confidence: 59%
“…The simplified GMTIV score is similar to the MEST score used in the estimation of IgAN severity, according to the presence of mesangial (M), endocapillary (E), glomerular sclerosis (S), and tubular atrophy (T). 16,17 The prevalence of obesity has increased dramatically. This worldwide obesity epidemic has produced more medical attention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IR can induce glucose metabolism imbalance, causing excessive glycosylation, which can promote smooth muscle cell proliferation, collagen crosslinking, and collagen deposition, as well as triggering inflammation and oxidative stress [ 25 ]. In addition to its role in hyperglycaemia, IR plays an important role in hyperlipidaemia, which induces oxidative stress and apoptosis, causing the initiation of atherosclerosis and podocyte injury via fibrosis, inflammation and apoptosis [ 26 , 27 ]. Moreover, mounting evidence has revealed that IR can induce an increased production of glycosylated products and free radicals, leading to nitric oxide (NO) inactivation.…”
Section: Discussionmentioning
confidence: 99%